2013
DOI: 10.1111/jhn.12125
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake in adolescent girls and boys diagnosed with coeliac disease at an early age is mostly comparable to their non‐coeliac contemporaries

Abstract: Nutrient intake of adolescent girls and boys with CD was mostly comparable to intakes of NC controls. Dietitians should take the opportunity to reinforce a generally healthy diet when providing information about the gluten-free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
12
34
0
Order By: Relevance
“…In our study, children with CD who followed a GFD for more than 6 months had a lower intake of folic acid, magnesium and selenium than the control group. These data are consistent with those reported in other studies [30][31][32] that described a lower intake of folic acid, magnesium and selenium, among other micronutrients. Folate intake in children with CD has been poorly investigated, and there are data that indicate lower folate intake with a GFD [33].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, children with CD who followed a GFD for more than 6 months had a lower intake of folic acid, magnesium and selenium than the control group. These data are consistent with those reported in other studies [30][31][32] that described a lower intake of folic acid, magnesium and selenium, among other micronutrients. Folate intake in children with CD has been poorly investigated, and there are data that indicate lower folate intake with a GFD [33].…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study we confirmed this finding; however, importantly, the dietary intake of a same-aged non-coeliac reference group had the same natural drawbacks ( 14 ) .…”
supporting
confidence: 79%
“…A variety of studies have shown that children and adults with CD on the GFD have low intakes of fibre, folate, vitamin D, and vitamin K and high intakes of protein, total sugar, and saturated fat [7][8][9][10][11]. However, little is known regarding the quality of nutrient intake in children and adolescents in Canada with CD on the GFD.…”
Section: Introductionmentioning
confidence: 99%